STRATEGI PENINGKATAN PENDAPATAN PETANI PADI SAWAH DI KABUPATEN PASURUAN (Strategy To Improve Farmers’ Income Rice Fields In Pasuruan Regency) - ALWI, ISA; SUMARNO, SUMARNO; SETIAJI, JATMIKO (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2026)
This study aims to examine the income levels of rice farmers and to map the internal and external factors that influence farming activities. The research was conducted in Pasuruan Regency, East Java, with three sub-districts selected using purposive sampling technique, namely Kraton, Wonorejo, and Kejayan sub-districts, with a total of 72 farmers as respondents determined using the Slovin formula. Data collection was conducted thru structured interviews based on a Likert scale questionnaire, while data processing used a SWAT analysis approach combined with IFAS and EFAS matrices. The research findings revealed that: (1) the average income of rice farmers in the study location is Rp6,824,000 per planting season with an average yield of 2,300 kg per planting season on an average land area of 0.3 hectares; (2) identified strengths include farmer motivation (score 4), farming experience (score 4), soil fertility (score 3), and the application of agricultural machinery technology (score 3), while weaknesses include limited business capital, inefficiency in fertilizer use, narrow farming land, and weak farmer group dynamics; (3) opportunity factors include access to KUR Tani financing (score 4), availability of superior varieties (score 4), availability of fertilizers and pesticides (score 4), and government policy support (score 3), while threat factors include rainfall fluctuations, low government purchase prices (HPP) for rice, scarcity of agricultural labor, and attacks by plant-disturbing organisms (OPT); (4) based on the IFAS matrix (score difference 0.90) and the EFAS matrix (score difference 1.21), the strategic position is in Quadrant I, so the recommended priority strategy is an aggressive strategy (SO) thru optimizing production facility subsidies, accelerating the adoption of modern agricultural machinery, and strengthening farmers' access to capital.